2019
DOI: 10.1002/ece3.5629
|View full text |Cite
|
Sign up to set email alerts
|

Selection on multiple sexual signals in two Central and Eastern European populations of the barn swallow

Abstract: Variation in intensity and targets of sexual selection on multiple traits has been suggested to play a major role in promoting phenotypic differentiation between populations, although the divergence in selection may depend on year, local conditions or age. In this study, we quantified sexual selection for two putative sexual signals across two Central and East European barn swallow (Hirundo rustica rustica) populations from Czech Republic and Romania over multiple years. We then related these differences in se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The barn swallow is a well-studied (17–22) migratory passerine bird with six recognised subspecies in Europe, Asia, Africa and the Americas (23). While still poorly understood, recent studies have started to shed light on its genetics (18,2429). The barn swallow demographic history reconstructed from genomic data suggests that the current barn swallow distribution derives from a relatively recent expansion, probably driven by the spread of human settlements providing more nesting opportunities (28,30).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The barn swallow is a well-studied (17–22) migratory passerine bird with six recognised subspecies in Europe, Asia, Africa and the Americas (23). While still poorly understood, recent studies have started to shed light on its genetics (18,2429). The barn swallow demographic history reconstructed from genomic data suggests that the current barn swallow distribution derives from a relatively recent expansion, probably driven by the spread of human settlements providing more nesting opportunities (28,30).…”
Section: Introductionmentioning
confidence: 99%
“…Because of its strong association with humans, the barn swallow (Hirundo rustica) is a well-suited model to investigate the evolution and genetic bases of behaviours correlated to synanthropy. The barn swallow is a well-studied (17)(18)(19)(20)(21)(22) migratory passerine bird with six recognised subspecies in Europe, Asia, Africa and the Americas (23). While still poorly understood, recent studies have started to shed light on its genetics (18,(24)(25)(26)(27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have identified male plumage traits associated with strong female preferences and increased fitness (Byers et al, 2010; Møller, 1988; Rodríguez et al, 2006; Ryan et al, 2019; Searcy & Andersson, 1986). In contrast, relatively few studies have found relationships between female visual signals and fitness proxies, but see: (Amundsen et al, 1997; Bulluck et al, 2017; Cain & Ketterson, 2011; Jawor et al, 2004; Pap et al, 2019). Likewise, many studies have examined the fitness correlates of male song (Catchpole & Slater, 2003; Gil & Gahr, 2002), but only a handful have looked at how female song impacts fitness (Brunton et al, 2016; Cain et al, 2015; Kleindorfer et al, 2016b; Krieg & Getty, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified male plumage traits associated with strong female preferences and increased fitness (Byers et al, 2010;Møller, 1988;Rodríguez et al, 2006;Ryan et al, 2019;Searcy & Andersson, 1986). In contrast, relatively few studies have looked for or uncovered relationships between female visual signals and fitness proxies, but see: (Amundsen et al, 1997;Bulluck et al, 2017;Cain & Ketterson, 2011;Jawor et al, 2004;Pap et al, 2019). Likewise, many studies have examined the fitness correlates of male song (Catchpole & Slater, 2003;Gil & Gahr, 2002), but only a handful have looked at how female song impacts fitness (Brunton et al, 2016;Cain et al, 2015;Kleindorfer et al, 2016;Krieg & Getty, 2016).…”
mentioning
confidence: 99%